2019
DOI: 10.1021/acs.jpcc.9b05394
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Decomposition of Ethanol on Cu2O(111) and (100)

Abstract: Ethanol dehydrogenation on metal oxides such as Cu2O is an important reaction for the production of renewable energy by fuel cells both via the production of H2 fuel and via application in direct alcohol fuel cells. To better understand this reaction, we studied the adsorption, dissociation, and desorption of ethanol on Cu2O­(111) and (100) surfaces using high-resolution photoelectron spectroscopy, vibrational sum-frequency generation spectroscopy, and temperature-programmed desorption accompanied by density f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The effects of onsite Coulomb interactions of the localized d orbital and exchange interactions for copper oxides were considered by employing the PBE + U method. The Hubbard parameter of U – J was set to 3.6 eV based on that reported in the literature, which was determined from the electrostatically embedded Hartree–Fock calculations using the method exploited by Mosey and co-workers . Atomic structural optimization was relaxed using the damped molecular dynamics method until the force difference between the two steps was ≤0.02 eV/Å, and a Gaussian smearing of σ = 0.2 eV was applied to accelerate the convergence.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of onsite Coulomb interactions of the localized d orbital and exchange interactions for copper oxides were considered by employing the PBE + U method. The Hubbard parameter of U – J was set to 3.6 eV based on that reported in the literature, which was determined from the electrostatically embedded Hartree–Fock calculations using the method exploited by Mosey and co-workers . Atomic structural optimization was relaxed using the damped molecular dynamics method until the force difference between the two steps was ≤0.02 eV/Å, and a Gaussian smearing of σ = 0.2 eV was applied to accelerate the convergence.…”
Section: Methodsmentioning
confidence: 99%
“…Copper is known to be an effective catalyst of ethanol dehydrogenation (Equation ( 2)) [11]. The participation of Cu 2 O in ethanol dehydrogenation (Equation (2)) has also been examined [37]. Sato et al [38] suggested that the Cu + /Cu 0 pairs on a Cu-based catalyst (Cu/SiO 2 ) exhibited high selectivity toward acetaldehyde in ethanol conversion reaction.…”
Section: Effect Of Lialo 2 Support and Cu/ni Catalystsmentioning
confidence: 99%
“…an enhanced activity increasing from {100} to {111} facets associated with cubic and octahedral morphologies, respectively, was reported. [1] Moreover, surface energies, [7] binding of solvent molecules (most importantly ethanol molecules) [8,9] as well as the deposition of noble metals on the different crystal planes also show facet-dependent characteristics. [7,10,11] Hence, tailoring the morphology of the nanoparticle has opened up new routes towards the synthesis and design of Cu2O-based multicomponent (photo)catalysts.…”
Section: Introductionmentioning
confidence: 99%